Accent Matters. Papers on Balto-Slavic Accentology: Edited by Tijmen Pronk and Rick Derksen. Third International Workshop on Balto-Slavic Accentology (IWoBA) held at Leiden University July 27 – 29, 2007. Amsterdam – New York: Editions Rodopi B.V., 2011. 366 pp. - K. Bogatyrev, Konstantin (Slavia Centralis, 2020)
The paper presents a volume containing a diverse collection of articles presented at a workshop on Slavic accentology, which is part of the ongoing international efforts to consolidate research in the field of Balto-Slavic prosody and related fields.
Keywords: Accent Matters. Papers on Balto-Slavic Accentology; review; Balto-Slavic prosody